Percutaneous endoscopic creation of a neoinfundibulum for a calyceal diverticulum: A case report and review of the literature - Das, Arighno; Blumenthal, Zoe; Monroe, Eric; Farhat, Walid A.; Bhatia, Vinaya P. (Frontiers in Urology, 2022)
Introduction: Calyceal diverticula (CD) are cystic structures within renal parenchyma which likely result from inappropriate interaction between the ureteric bud and metanephric blastema during development, and, if obstructed, may cause problems which include flank pain, urinary tract infections, gross hematuria, or nephrolithiasis. Herein, we present the results of percutaneous management of an obstructed calyceal diverticulum causing recurrent flank pain and infections in a 17-year-old female. Case Summary: The patient initially presented with febrile pyelonephritis, at which time an ultrasound was concerning for an abscess vs. infected cyst. She underwent percutaneous drain placement with IV antibiotics and improved. Three years later, she re-presented with similar symptoms. After a similar treatment course, a sinogram revealed communication of the cystic-appearing lesion with the proximal ureter, confirming a diagnosis of calyceal diverticulum. The patient opted for endoscopic management. An initial attempt at ureteroscopy was unsuccessful due to both the small ureteral caliber as well as the stenotic infundibular os. A repeat attempt at percutaneous management revealed a stenotic infundibulum which could not accommodate a wire. A holmium laser fiber was used to created a neoinfundibulum from the diverticulum to the renal pelvis adjacent to the stenotic infundibular os. Follow-up retrograde pyelography and ultrasonography confirmed an interval decrease in size of the infundibulum, and the patient’s infectious symptoms and pain resolved. Discussion: CD are a rare anomaly and infrequently reported in the pediatric population. Percutaneous management of CD in adults has been well described in the literature2-5. Direct percutaneous management of CD involves access into the CD and ablation of the CD cavity to prevent re-accumulation of urine. Previous studies done in adults have suggested that stone free rates from this range from about 80-100%. Diverticular obliteration, as measured by post-operative CT scans, also appears to feasible in a percutaneous, antegrade approach, with complete diverticular obliteration rates ranging from 60-100%. Our case demonstrated a successful decrease in size from the original diverticulum (9cm) to a smaller size (2cm). Future studies with longer follow-up will need to ascertain if percutaneous management of symptomatic CD is effective in the pediatric population.